Vanadium phosphate catalyst synthesized by organic method using sonicated V2O5 for selective oxidation of n-butane to maleic anhydride - Suhaimi, Suhaizam Shahrul Affendy (2012)
Selective oxidation of alkanes by heterogeneous catalytic reaction has been one of the most active areas in the field of catalysis. The selective oxidation of n-butane to maleic anhydride (MA) over vanadium phosphate catalyst (VPO) was recognized as one of the most studied reaction for the past few decades. A number of new methods were suggested in the preparation of VPO catalyst to increase the performance of the catalyst in terms of activity and selectivity. In this study, VPO catalysts were synthesized using sonicated V2O5. V2O5 obtained from the commercial sources was treated using ultrasound pretreatment with two different mineralizers (NaCl and NaNO3) in several durations (30-120 min). XRD patterns of the sonicated V2O5 gave similar structure like the pure V2O5 phase and prolonged the duration of sonication had led to an increase in the intensity of the diffraction peaks, which indicated the high crystallinity of the sonicated V2O5. SEM micrographs showed that longer periods of sonication pretreatment produced sonicated V2O5 with higher amount of plate-like crystals. TEM micrographs showed that due to the sonication pretreatment, V2O5 with nano scale size and in the form of wires was successfully synthesized. Prolonged duration of sonication up to 120 min also had reduced the diameter of the sonicated V2O5 to below than ~20 nm. Further study on the effect of sonication pretreatment to the physical and chemical properties of vanadium phosphate catalyst (VPO) was performed by using the sonicated V2O5 for the synthesis of VOHPO4∙0.5H2O precursor. Comparative study between the sonicated VPO catalysts and VPO synthesized using conventional method (organic route) was done by using XRD, BET, bulk composition analysis, volumetric titration method analysis, SEM and H2-TPR. Results showed that the application of sonicated V2O5 had reduced the crystallite size of the final VPO catalyst and increased the total surface area of the catalyst. TPR analysis also showed that the reactivity and reducibility of oxygen species for VPO catalyst synthesized by sonicated V2O5 was slightly improved, where the reduction peaks which correlated to the V5+ and V4+ phases were shifted to much lower temperatures. High amount of oxygen species at lower temperature will increase the availability of oxygen for the breaking of C-H bond during the partial oxidation of n-butane. As evident, the MA selectivity for VPO60 tremendously increased up to 52% while the n-butane conversion of VPO90 had greatly increased up to 43% during the selective oxidation of n-butane to MA.